Oen Boen Ing’s Role during Indonesian Independence Revolution Period on 1945-1949 - Herdadian, Herdiona Hellen; Widiyanta, Danar (JURNAL HISTORICA, 2024)
Oen Boen Ing, or better known in the public as â€œdr. Oenâ€ is an Indonesian National Figure of Chinese ethnicity who has played an active role in his service to the nation and state. Especially in the health sector. Due to his deep love for Indonesia, dr. Oen was also often given the nickname as a kind doctor, a revolutionary patriot, and even a doctor for the poor during his lifetime. Dr. Oen is known for his services without asking for compensation from the community for his service. Across 5 periods, dr. Oen was given an award for his series of sacrifices for the Indonesian medical world and was respected by the community. Especially by the people of Surakarta and his name was immortalized, one of them in the naming of a large hospital in Surakarta, "dr. Oen Hospitalâ€, as well as a form of final respect for him. This research aims to find out a brief biography of dr. Oen, the role of dr. Oen specifically during the War of Independence in Indonesia and various awards were given as a sign of respect from the Indonesian government and society for dr. Oen. This article was written based on the critical history method through the stages of topic selection, heuristics, verification, interpretation and historiography.